Long-term audit of the use of fresh frozen plasma in a university hospital - Abdel Galil M. Abdel Gader, PhD; Abeer K. Al-Ghumlas, PhD; Abdul Kareem M. Al Momen, FRCPC; Sitel Banat A. Awadalla, PhD; Motasim Badri, PhD (Journal of Taibah University Medical Sciences, 2017)
Objectives: There is universal concern about the inappropriate use of fresh frozen plasma (FFP). This study aimed to determine the extent of the inappropriate use of FFP at a university hospital in KSA. Methods: Medical records on the annual use of FFP were analysed from 1986 to 2007. Then, the results of the coagulation screening tests were extracted from the medical records of 531 consecutive patients in various departments of the hospital. Results: As many as 68,480 FFP units were used during the 22 year study period. Consumption increased and then plateaued in 1995, but dropped dramatically by 30.9% and reached its lowest level in 2000. There was also a concomitant and overlapping drop in both FFP usage and the hospital mortality rate per patient admission. One-thousand-six-hundred-twenty FFP units were issued for 531 patients. Coagulation testing, before and after infusion, was adopted in almost all patients in the Department of Obstetrics and Gynaecology, in 90% of patients in the Department of Surgery and in approximately 70% of patients in other departments. Conclusions: Significant inappropriate use of FFP at our institute has been made evident by examining the remarkable drop in use following the universal “HIV scare” of the early 1990s. The resulting drop in the hospital mortality rate, accompanying the simultaneous drop in FFP use, reflects the benefits of resorting to the use of less blood therapy. Coagulation testing was used to a satisfactory extent. Transfusion audits and educational programs could result a better use of FFP.